On-Farm evaluation of different storage materials for the management of four stored grain insect pests on stored wheat (Zoo Botanica, 2025)
Four standard storage bags, namely polyethylene (PE), polypropylene (PP), hermetic bag (HB), and jute bag (JB), were evaluated for the management of insect pests of stored grains. Efficacy parameters were recorded as percent weight losses, damaged grain percentage, and population buildup over time intervals. Already infested wheat was stored in four bag types at two locations to record the effectiveness of each bag. Results showed that damages such as percent weight loss and percent grain damage made by insects were more in polyethylene as compared to polypropylene, jute, and the hermetic bag. Populations were recorded dead only in the hermetic bag at each time interval. The hermetic bag proved lethal for stored grain insect pests’ development, and insect populations were found 100% dead in hermetic bags with no single account of a live insect over all-time intervals, viz. 30, 60, and 90 d. Grain moisture fluctuated in all bags while in a hermetic bag, grain moisture decreased and then became constant. All types of damages were recorded more at grain market in Bahawalnagar which is a hotter place than the Rice Research Institute, Kala Shah Kaku. Results indicated that the hermetic bag proved to be the best material for stored grains insect pests’ management
Keywords: Tribolium castaneum; Sitophilus oryzae; Sitophilus granaries; insect pest management; storage materials